Detection of immunogenic protein from salivary gland of Aedes albopictus - Oktarianti, Rike; Khasanah, Rochmatul Nuryu; Wathon, Syubbanul; Senjarini, Kartika (Universa Medicina, 2021)
BackgroundDengue virus is transmitted by several species of Aedes mosquitoes, with Aedes albopictus as secondary vector. During blood feeding, these vectors inject saliva into the vertebrate hosts. The saliva contains anticoagulant, anti-inflammatory and immunogenic factors. The objective of this research was to detect immunogenic proteins from Ae.albopictus salivary glands reacting with sera of people living in dengue endemic areas. MethodsThe identification of immunogenic proteins of Ae. albopictus salivary gland used one-dimensional gel electrophoresis (sodium dodecyl sulfate polyacrylamide gel electrophoresis), and western blot analysis, respectively. To determine the immunogenic nature of the candidate proteins, the antigens from the salivary gland of Ae. albopictus were reacted with sera from healthy persons, dengue hemorrhagic fever (DHF) patients, and neonates, each of the groups comprising 10 samples. ResultsThe protein profiles of Ae. albopictus salivary glands showed 13 bands with molecular weights from 16 kDa up to 97 kDa, i.e. 16, 17, 26, 28, 31, 32, 45, 55, 60, 67, 73, 76, and 97 kDa. According to western blot analysis result, the 31 kDa proteins were recognized in all endemic population sera, both in DHF patients and healthy persons. In contrast, protein bands of 47 and 67 kDa were only recognized by the sera of DHF patients. ConclusionThree immunogenic proteins of 31, 47 and 67 kDa were detected from Ae. albopictus salivary glands. These immunogenic proteins may be developed as candidate biomarkers for bite exposure to Ae. albopictus and as vector-based DHF vaccines.